Disaster management: identifying knowledge of emergency nurses and community health nurses and its predictors in Malaysia - Ismail, Aniza; Faisal Ghazi, Hasanain; Ismail, Mohd Saibon; Ahayalimudin, Nurul'Ain (Malaysian Public Health Physicians’ Association, 2016)
As a front-liner in healthcare services, nurses play an important role in managing disaster victims. Thus, it is crucial for nurses to be prepared when facing disaster. The aim of this paper is to determine the knowledge of emergency nurses (EN) and community health nurses (CHN) with respect to disaster management, as well as identify predictor factors. This comparative cross-sectional study was conducted between October and November 2011. The 17-items of the self-developed questionnaire in assessing knowledge towards disaster management were distributed to randomly selected nurses from 10 emergency and trauma departments (132 respondents) and 8 health clinics (264 respondents) in one of the state in Malaysia. The results showed that both groups had a comparable median score on knowledge, 58.82 with interquartile range (IQR) = 52.94-70.58 for EN and IQR = 48.53-69.12 for CHN. No significant difference in knowledge was identified within these groups, with approximately 59.1% having inadequate knowledge of disaster management. Attending disaster-related education/training was identified as a predictor factor for adequacy of knowledge among EN with significant value of p < 0.01, (AOR) of 3.807, 95% (CI) of 1.584-9.153) and CHN (p < 0.001, AOR = 3.511, 95% CI = 2.097-5.881). As conclusion, emergency and community health nurses have inadequate knowledge with regard to disaster management, and it has been demonstrated statistically that adequacy of knowledge is driven by attending disaster-related education/training, which predicts knowledge level. Therefore, it is paramount for organizations to conduct disaster-related education/training to improve nurses' knowledge.